Weld metal irradiation embrittlement analysis in the range of over-design neutron fluences - L. I. Chyrko; V. M. Revka; Yu. V. Chaikovskyi; M. G. Goliak; O. V. Trygubenko; O. V. Shkapyak (Ядерна фізика та енергетика)
The comparison of experimental values of the critical brittle temperature ΔTF and reference temperature ΔT0 of VVER-1000 reactor vessel weld metal with an elevated content of manganese and nickel is performed. ΔTF and ΔT0 values are defined proceeding from the standard impact bend Charpy and Charpy cracked fracture toughness specimen tests, respectively. Specimens were irradiated in industrial reactors in the frame of surveillance specimen program up to the fast (E ≥ 0.5 MeV) neutron fluences corresponding to the NPP long term operation period. The research results showed the shifts ΔTF and ΔT0 to agree with each other. Besides, it was discovered that in the range of over-design fluences the design embrittlement model has a tendency to underestimate the critical brittle temperature shift.